P320 Developing an IBD inception pathway: a streamlined pathway to IBD diagnosis in the COVID era. (19th June 2022) - Rimmer, Peter; Cheesbrough, Jonathan; Quraishi, Mohammed Nabil; Sharma, Naveen; Cooney, Rachel; Kane, Kate; Cooper, Sheldon; Boulton, Ralph; Love, Melanie; Iqbal, Tariq
Abstract : Introduction: We have long aspired to deliver a fast track 'Inception' clinic for suspected IBD referrals. The urgency heightened in view of excessive outpatient (9 weeks urgent, 35 weeks routine) and endoscopy delays at our trust. We present our progress with this unique cohort who developed symptoms during the recent pandemic. Methods: All GP referrals were screened by senior clinicians and referrals suggestive of IBD were streamed to a dedicated IBD Inception clinic. Internal referrals and those for patients following 'Two-week Wait' colonoscopy were passed to a dedicated IBD Fellow who undertook further telephone triage of all referrals with clinics scheduled in order of clinical priority. Patients were invited to participate in an ongoing research programme. Initial diagnosis and treatment was overseen by the IBD Fellow (and supervising consultant) with care repatriated to a named consultant for long term care, heavily supported by IBD nursing colleagues, as described in figure 1 Results: Implemented in January 2021, 236 referrals have been managed on the treatment pathway. For GP referrals, median referral to review was 40 days (range 5 – 200). However, once the referral reached the IBD team, the wait fell to a median 17 days (0 – 127). After review, median wait was 26 days (0 – 170) for lower GI endoscopy. Of the 236 referrals, 55% now have a confirmed diagnosis of IBD, 65 with UC and 67 with Crohn's. 122 of these patients have enrolled into active research projects. of those diagnosed with IBD, treatment 'escalation' has been undertaken in 50 patients after a median 74 days (7 - 287) from treatment initiation. of these, 31 have commenced a biologic with a further 9 waiting their first dose. In these patients, the Median time from first pre-diagnosis outpatient review to starting a biologic was 107 days (14 – 301). Conclusions: Set against our trust figures, this data demonstrates that with a dedicated resource targeting suspected IBD, timely diagnosis and treatment is possible. Unacceptable delays remain within NHS processes handling referrals from Primary Care. This pathway, with inter-departmental cooperation, can improve the utilization of clinical resource for those most in need at a time of system pressure. Implementation of this pathway has now expanded across trust sites with further data on this unique adult cohort to follow. Having a dedicated fellow will not be realistic for all, but dedicated programmed activity may be. With whole departmental buy in and MDT integration, this approach has the capacity to enhance patient experience. This however remains to be demonstrated within our cohort.